Al-Juhūd al-Fikrīyah wa al-Iṣlāḥīyah al-Ḥukūmīyah min al-‘Ulamā’ al-Malayūwīyīn Maṭla’ al-Qarn al-‘Ishrīn - Abbas, Eeman Mohd.; Jasim, Layth Suud (Studia Islamika, 2007)
This article focuses on the role of the four lslamic reformers during the Iate 19th century and early 20th century. These four scholars include aI-Syaikh Ahmad ibn Muhammad Zayn al-Fathany (1273-1325 H/1865-1908 M); al-Syaikh al-Murabbi Muhammsd Sa'id al-Lanaqi (1292-1355 H/1875-1926 M); Tok Kenali (1287-1352 H/1870-1933 M); and al-Syaikh Thahir JaIal aI-Din al-Falakial-Azhari (1286-1376 H/1869-1956). These four Malay scholars led the reformist push at the same time of the arrival of the colonial powers from Europe. They inspired the people to oppose the colonialists, be it through education and knowledge, or through culture.DOI: 10.15408/sdi.v14i1.561